Trustworthy Execution on Mobile Devices - Vasudevan, Amit; McCune, Jonathan M.; Newsome, James (SpringerBriefs in Computer Science, 2014)
This brief considers the various stakeholders in today's mobile device ecosystem, and analyzes why widely-deployed hardware security primitives on mobile device platforms are inaccessible to application developers and end-users. Existing proposals are also evaluated for leveraging such primitives, and proves that they can indeed strengthen the security properties available to applications and users, without reducing the properties currently enjoyed by OEMs and network carriers. Finally, this brief makes recommendations for future research that may yield practical and deployable results.